TEORI MUTASYÀBIH MAŠÀNÌ (Tawaran Teori Baru dalam Studi Al-Qur’an) - Abdurrahman S.HI.,M.Pd (El-QUDWAH, 2013)
TEORI MUTASYÀBIH MAŠÀNÌ (Tawaran Teori Baru dalam Studi Al-Qur’an) Oleh: Abdurrahman, S.H.I., M.Pd. Dosen STAI Al-Qolam Gondanglegi Malang Email: abdurrahman@staialqolam.com   Astract God proclaims the Quran as a holy book with a mutasyàbih and masani character. According to the common transliteration, referred to a book that uses repetition system (mašànì), with editorial and content similarity, so there is no contradiction in it (mutasyàbih).The two charactersbecomes a powerful system in all parts of the Qur'an,aspecially when correlated with the concept of "the holding part" attached to seven paragraph (sab’an min al-mašànì) called al-fàtihah, and when any interpretation of the mutasyabih must be returned in the muhkam. This brings authors on the assumption that the character mutasyàbihmašànì is a model of Qur’anic representation that if traced with an inductive approach will discover a new concept, or even a new theory which can be compared with other major theories in Qur’anic Studies. And the authors offer al-fàtihah as early foothold inductive search project to build such new theory. Keywords: Mutasyàbih Mašànì, Sab’an min al-Mašànì, New Theory, Qur’anic Studies